ANALISA METODE DATA MINING PADA PENGELOMPOKAN LAPANGAN KERJA INFORMAL SEKTOR NON-PERTANIAN - Khairunnissa Fanny Irnanda; Agus Perdana Windarto; Dedy Hartama; Anjar Wanto (STMIK Budi Darma, 2019)
The objective of the study is to classify informal employment in non-agricultural sectors. Data sources are obtained from the Central Statistics Agency (BPS). The data used is the proportion of employment for informal non-agricultural sectors (2015-2018), consisting of 34 Provinces in Indonesia. The Method used to solve the problem is datamining technique K-Medoid. The results of the research showed that the percentage of informal employment of non-agricultural sectors based on the lowest region became a record for the government to further increase human resources and more open the field jobs in non-agricultural sectors, among others.Keywords: Informal sector, Datamining, K-Medoid, Clustering, Non-Agricultural